Maternal pertussis is hazardous for a newborn: a case report - Armangil, Didem; Tekinalp, Gülsevin; Yurdakök, Murat; Yalçin, Ebru (The Turkish Journal of Pediatrics, 2010)
Pertussis, or whooping cough, a highly contagious disease caused by Bordetella pertussis, is making a comeback globally and nationally in spite of reasonable vaccination coverage. Worldwide, there have been increasing reports of Bordetella pertussis infection among adolescents and adults, but the peak incidence and highest mortality occur among infants. We report a 19-day-old female infant presenting with progressive respiratory failure. The mother was the only familial contact who complained of mild cough. However, occasional apneic episodes with cyanosis and peripheral lymphocytosis prompted us to examine the presence of Bordetella pertussis, which remains a significant cause of morbidity and mortality in unimmunized infants. Understanding the source of pertussis transmission to infants may provide new approaches to prevent pertussis in the most vulnerable infants. Various potential strategies have been reviewed or recommended in countries with the aim of better protecting infants against pertussis. Public health measures to prevent the disease could be strengthened and booster vaccinations against pertussis considered.